Sustainable agriculture for health and prosperity: stakeholders' roles, legitimacy and modus operandi. Issue 7 (2nd October 2020) - Hellin, Jon; Balié, Jean; Fisher, Eleanor; Blundo-Canto, Genowefa; Meah, Nafees; Kohli, Ajay; Connor, Melanie
ABSTRACT: Food systems need to focus more on health, prosperity, and environmental sustainability. This requires changes in what, where, how and by whom food is produced, marketed, and consumed. Interdisciplinary research and trans-disciplinary collaboration are needed. Stakeholders need to agree on their respective roles, values, responsibilities and modus operandi so that research better responds to real-world challenges and opportunities. This viewpoint argues that this is especially the case in the Global South post Covid-19. Without these changes, there will continue to be unrealistic expectations of impact from agricultural research, and disappointment when these are not realised.